Dysbiosis and depressive disorders. Survey review - Inga Janik; Martyna Maciejewska; Katarzyna Korabiusz; Agata Wawryków; Agnieszka Wilczyńska; Monika Stecko; Anna Fabian-Danielewska (Kazimierz Wielki University, 2019)
A significant increase in the incidence of depression, change of lifestyle and nutrition, forces researchers to seek understanding of the various mechanisms of the formation of such a disorder. Numerous studies draw attention to dysbiosis - a disorder of the composition and function of the intestinal microflora. In current studies, strong correlations can be observed between microbiota disorders and the occurrence of autoimmune and inflammatory diseases.